Spatial Distribution of Dengue Hemorrhagic Fever (DHF) Casesin Sragen - Dodiet Aditya Setyawan; Wiwik Setyaningsih (Universitas Ahmad Dahlan, 2021)
Background: Dengue Hemorrhagic Fever (DHF) had still become a health problem that often occurred and not least caused death for Indonesia especially in Sragen, Central Java. Distribution of DHF cases in an area could be described using Spatial analysis with Geographic Information Systems (GIS). Objective: This study aimed to provide spatial distribution of Dengue Hemorrhagic Fever cases and regional endemicity of DHF in Sragen during 2016-2018 using Geographic Information Systems. Method: Descriptive research design with Cross-Sectional approach using GIS was used to get the description of spatial distribution of dengue and the region endemicity of dengue in Sragen. The sample used was Saturated Sample which was secondary data about the incidence of DHF from District Health Office of Sragen from 2016 to 2018 totaling 1,349 cases. The subjects consisted of geographical areas which consisted of 20 subdistricts with DHF case. The collected data were analyzed descriptively by displaying a frequency distribution table and description of spatial distribution using Geographic Information System. Results: The results showed that the spatial distribution of DHF was spread randomly in all districts in Sragen. The average incidence rate (IR) of DHF during the last 3 years in Sragen was > 50 / 100,000 population. Spatial description showed that 58 villages out of 208 villages in Sragen were DFH endemic areas and generally all subdistricts in Sragen were endemic areas of DHF. Conclusion: Spatial description of DHF in Sragen showed that all subdistricts in Sragen were endemic areas for DHF.